EFFORT TO INCREASE THE DEVELOPMENT OF THE GAMPONG MEUNASAH MEE COMMUNITY IN THE FIELDS OF EDUCATION, ECONOMY AND SOCIAL IN THE KEMBANG TANJONG DISTRICT OF PIDIE DISTRICT THROUGH REAL WORK COLLEGE STUDENTS (KKN) - Sufyan; Maimun; Adi Ahmad; Tarmizi; Riyan Maulana; Muhammad Yassir; Nasruddin; Deni Trianda Pitri; Rifka Nadia (Jurnal Pengabdian Bangsa, 2024)
Real Work Lecture (KKN) is a community service model that focuses on empowering families in educational, economic, social and environmental aspects. KKN places students living with the community in forming institutions or community development, especially existing community institutions. Through this KKN, students together with the community identify problems and mobilize all existing potentials for the progress of the community. Based on this, we propose a work program in Gampong Meunasah Mee, Kembang Tanjong District, Pidie. The purpose of this work program is to provide evidence of devotion to Gampong Meunasah Mee, especially the community and village officials. This activity can be carried out well and produces several KKN student activity programs in the field of Education, namely teaching TPA, teaching the Koran, teaching computers and organizing volleyball tournaments and social services. This activity targets children, parents of students, the community and also, village officials in Gampong Meunsah Mee, Kembang Tanjong District, Pidie Regency. This activity is beneficial for the village community for future development and progress, especially for the apparatus. This activity is expected to provide provisions for the village community and village officials in managing and organizing the village well.